Book review: David W. Westbrook. Navigators of the Contemporary: Why Ethnography Matters - Edward Dutton (Suomen Antropologi)
WESTBROOK, DAVID W. Navigators of the Contemporary: Why Ethnography Matters. Chicago: University of Chicago Press, 2008. Pp. 152. ISBN: 978-0-226-88751-7 (cloth); ISBN: 978-0-226-88752-4 (paperback).